Anhedonia induced by high-fat diet in mice depends on gut microbiota and leptin. (1st February 2022) - Hassan, Ahmed M.; Mancano, Giulia; Kashofer, Karl; Liebisch, Gerhard; Farzi, Aitak; Zenz, Geraldine; Claus, Sandrine P.; Holzer, Peter
ABSTRACT: Objectives: Imbalanced nutrition and obesity are risk factors for depression, a relationship that in rodents can be modeled by depression-like behavior in response to high-fat diet (HFD). In this work, we examined the role of the intestinal microbiota and the adipocytokine leptin as potential mediators of the effects of HFD to induce anhedonia-like behavior and reduce self-care in mice. Methods: Male mice were fed a control diet or HFD (60 kJ% from fat) for a period of 4 weeks, after which behavioral tests and molecular analyses (gut microbiome composition, intestinal metabolome, fecal fatty acids, plasma hormone levels) were performed. The role of the intestinal microbiota was addressed by selective depletion of gut bacteria with a combination of non-absorbable antibiotics, while the implication of leptin was examined by the use of leptin-deficient ob/ob mice. Results: Antibiotic treatment reduced the HFD-induced weight gain and adiposity and prevented HFD-induced anhedonia-like behavior and self-care reduction. These effects were associated with a decrease in fecal fatty acids and intestinal microbiota-related metabolites including short-chain fatty acids, glucose and amino acids. Gut microbiota depletion suppressed the HFD-induced rise of plasma leptin, and the circulating leptin levels correlated with the anhedonia-like behavior and reduced self-care caused by HFD. The anhedonic effect of HFD was absent in leptin-deficient ob/ob mice although these animals gained more weight and adiposity in response to HFD than wild-type mice. Discussion: The results indicate that anhedonia-like behavior induced by HFD in mice depends on the intestinal microbiome and involves leptin as a signaling hormone.